Foreign Ownership dan Earnings Management pada Perbankan Asean - Ghofar, Abdul (Akuntansi: Jurnal Akuntansi Integratif, 2023)
This research aims to examine the influence of foreign ownership on the earnings management of banking companies in the ASEAN region. The population is banking companies listed on the Stock Exchanges of four ASEAN countries: Indonesia, Malaysia, the Philippines and Thailand. We took 430 companies as samples for this research from these countries. This research took 5 (five) years. The results of the study found that foreign ownership has a negative relationship with earnings management because foreign ownership can reduce management actions to carry out earnings management; Foreign-owned banking companies have higher earnings quality in the first five years, and foreign investors' home countries that have a high CPI also have higher earnings quality. This research, based on the findings, can state that foreign investors can improve the effectiveness of governance and maintain earnings management.